Drug library screen reveals benzimidazole derivatives as selective cytotoxic agents for KRAS-mutant lung cancer. (1st June 2019) - Shimomura, Iwao; Yokoi, Akira; Kohama, Isaku; Kumazaki, Minami; Tada, Yuji; Tatsumi, Koichiro; Ochiya, Takahiro; Yamamoto, Yusuke
Abstract: KRAS is one of the most frequently mutated oncogenes in human non-small cell lung cancer (NSCLC). Mutations in KRAS are detected in 30% of NSCLC cases, with most of them occurring in codons 12 and 13 and less commonly in others. Despite intense efforts to develop drugs targeting mutant KRAS, no effective therapeutic strategies have been successfully tested in clinical trials. Here, we investigated molecular targets for KRAS-activated lung cancer cells using a drug library. A total of 1271 small molecules were screened in KRAS-mutant and wild-type lung cancer cell lines. The screening identified the cytotoxic effects of benzimidazole derivatives on KRAS-mutant lung cancer cells. Treatments with two benzimidazole derivatives, methiazole and fenbendazole—both of which are structurally specific—yielded significant suppression of the RAS-related signaling pathways in KRAS-mutated cells. Moreover, combinatorial therapy with methiazole and trametinib, a MEK inhibitor, induced synergistic effects in KRAS-mutant lung cancer cells. Our study demonstrates that these benzimidazole derivatives play an important role in suppressing KRAS-mutant lung cancer cells, thus offering a novel combinatorial therapeutic approach against such cancer cells. Highlights: Drug screening identified benzimidazole derivatives as selected candidate. Benzimidazole derivatives showed cytotoxic effects for KRAS-mutant cells specifically. Benzimidazole derivatives showed synergy combined with MEK inhibitor.